Instructional Leadership Based on the Iddhipada Iv Principles of School Administration Promoting Educational Innovation in Thungyai Cluster the Secondary Educational Service Area Office of Nakhon Si Thammarat: Instructional Leadership Based on the Iddhipada Iv Principles of School Administration Promoting Educational Innovation in Thungyai Cluster the Secondary Educational Service Area Office of Nakhon Si Thammarat - Saengmanee, Phonlavath; Sumetpariyattikun, Phrakhru; Samakkhi, Pricha (RATANABUTH JOURNAL, 2026)
This study aimed to: 1) examine the state of academic leadership of school administrators in promoting teachers’ educational innovation in the Thung Yai Cluster under the Secondary Educational Service Area Office of Nakhon Si Thammarat. 2) develop academic leadership guidelines based on the Iddhipada IV principles. And 3) present and evaluate these guidelines. A mixed-method research design was employed, integrating quantitative and qualitative approaches. The sample consisted of 60 participants, including school administrators and teachers. Key informants included seven monks/persons, and a focus group discussion was conducted with seven experts. The research instruments were implemented in three phases: a questionnaire, in-depth interviews, and an evaluation form. The findings revealed that: 1) the overall level of academic leadership in promoting teachers’ educational innovation was moderate (𝑥̄= 2.97, S.D. = 1.43) across all dimensions, including vision, mission, and goal setting; learning environment; curriculum and instructional management; and instructional supervision. Teachers’ educational innovation was also at a moderate level. 2) The proposed guidelines emphasized promoting teachers’ participation in defining school vision, mission, and goals; supporting curriculum and instructional development based on students’ learning outcomes; transforming instructional supervision from inspection to professional development; and fostering a supportive learning environment aligned with the school context. 3) The evaluation results indicated that the proposed guidelines were appropriate, feasible, and beneficial.